2020
DOI: 10.1177/1350650119899529
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of physicochemical and tribological properties of chaulmoogra (Hydnocarpus wightianus) oil as green lubricant base stock

Abstract: Due to environmental concerns, natural oils are increasingly being used as an alternative to mineral oil-based products such as lubricants. However, the use of edible oil for industrial application adversely affects their availability for edible purposes. Chaulmoogra oil is a non-edible oil obtained from the seeds of chaulmoogra tree that grows in wastelands. The fatty acid constituents of vegetable oils determine their properties. Presence of long-chain cyclic fatty acids like chaulmoogric acid, hydnocarpic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
(30 reference statements)
1
10
0
Order By: Relevance
“…However, the improvement in the WSD with the addition of ZDDP brings the WSD of the hazelnut comparable to the fully formulated oils. The experimental results of the current study are compared with the different tribological studies of petroleum-based oils under similar conditions (392 N, 1,200 RPM, 3,600 s and 75°C) as depicted by Figure 2 (Salaji and Jayadas, 2020; Hassan et al , 2016; Charoo and Wani, 2017; Zahid et al , 2015). It is observed that hazelnut oil mixed with ZDDP depict wear scars very close to the petroleum-based oils and has tremendous potential as a lubricant for industrial use.…”
Section: Resultsmentioning
confidence: 99%
“…However, the improvement in the WSD with the addition of ZDDP brings the WSD of the hazelnut comparable to the fully formulated oils. The experimental results of the current study are compared with the different tribological studies of petroleum-based oils under similar conditions (392 N, 1,200 RPM, 3,600 s and 75°C) as depicted by Figure 2 (Salaji and Jayadas, 2020; Hassan et al , 2016; Charoo and Wani, 2017; Zahid et al , 2015). It is observed that hazelnut oil mixed with ZDDP depict wear scars very close to the petroleum-based oils and has tremendous potential as a lubricant for industrial use.…”
Section: Resultsmentioning
confidence: 99%
“…One mg per mL of stock sample was prepared and 5 µL of this solution was injected in ultra-performance liquid chromatography (UPLC)-MS/MS and the mass spectra were recorded in positive and negative modes [14].…”
Section: Ms Of the Isolated Compoundmentioning
confidence: 99%
“…Quantitative estimation of isolated hydnocarpic from CMO acid using HPTLC The reference methodology was followed with a few modifications for HPTLC (CAMAG, Muttenz, Switzerland) fitted with winCATS 1.2.3 software for fingerprinting and quantitative analysis [14]. A stock solution (1.0 mg/mL) of the sample was prepared in UPLC-MS grade methanol and spotted in duplicate on a thin layer chromatography (TLC) plate in different concentrations such as 0.2, 0.4, 0.5, 1.0, and 2.0 µL, respectively.…”
Section: Ms Of the Isolated Compoundmentioning
confidence: 99%
“…Nanofluids formed from metal compounds also work well as lubricant additives [84][85][86][87]. Lubrication additives can also be obtained by modifying Zn/ZnO (zinc dialkyl dithiophosphates, ZDDP) [88][89][90][91][92][93][94]. Wu et al [95] synthesized lithium complex grease (LCG) added with carbon black (C), Fe 3 O 4 , and Al 2 O 3 nanoparticles on rolling bearing and found that nanoparticles were beneficial to enhance the friction and wear performance (see Fig.…”
Section: Lubricant Additivesmentioning
confidence: 99%